Bāṃlā nāṭake nārī-puruṣa o samāja - Āuyāla, Sājedula (Māolā Brādārsa, 2015)
Study on depiction of women, men and society in Bengali drama.
Includes bibliographical references (pages 159-162) and index
Keywords: Bengali drama; History and criticism; Women in literature; Men in literature; Society in literature